Rancang Bangun Tirai Otomatis Berbasis Arduino Uno R3 Dengan Sensor Ldr Dan Kendali Manual Via Bluetooth Hc-05 Melalui Aplikasi Mit App Inventor - Erik Agustian Yulanda; Sindi Kornelia Karolin (Journal of Innovative and Creativity, 2025)
The use of Automatic Curtains facilitates daily activities at school, in the library, and at home. This study designs a prototype of automatic curtains operated with a Light Dependent Resistor (LDR) sensor and a Bluetooth HC-05 module connected to a smartphone via the Mit App Inventori application. The method used in the automatic curtain research uses the LDR Sensor as an output to open and close the curtains automatically and uses Bluetooth HC-05 which is designed to be connected to a smartphone to open and close the curtains manually. Testing was carried out for experiments that the designed prototype functions according to the commands on the Arduino Uno R3 on the light captured by the LDR Sensor> 250 Lux then the curtain will be closed, and if the light captured by the dark LDR Sensor is <10 Lux then the curtain will open. This test aims to facilitate the learning and teaching process indoors by preventing the hot sun from entering the room and the curtain material used can be used as a Projector